2007
DOI: 10.1007/s00125-007-0676-2
|View full text |Cite
|
Sign up to set email alerts
|

Defective IGF2 and IGF1R protein production in embryonic pancreas precedes beta cell mass anomaly in the Goto–Kakizaki rat model of type 2 diabetes

Abstract: Aims/hypothesis The Goto-Kakizaki (GK) rat is a spontaneous model of type 2 diabetes. Defective beta cell mass detectable in late fetal age precedes the onset of hyperglycaemia. Our hypothesis was that an embryonic IGF production deficiency might be involved in beta cell mass anomaly in the diabetic GK rat. To test this, we evaluated during pancreatic organogenesis: (1) the beta cell development in GK rats on embryonic day (E) 13.5 and E18.5; (2) IGF2 and IGF1 receptor (IGF1R) pancreatic protein production on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 49 publications
5
55
0
Order By: Relevance
“…1 and Table 1). These data confirm and extend our earlier reports of decreased transcript levels of Pdx1, Neurog3 (also known as Ngn3) and Igf2 [16,18] and reduction in pancreatic IGF2 and IGF1R protein levels [16] in E18.5 GK stock fetuses.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…1 and Table 1). These data confirm and extend our earlier reports of decreased transcript levels of Pdx1, Neurog3 (also known as Ngn3) and Igf2 [16,18] and reduction in pancreatic IGF2 and IGF1R protein levels [16] in E18.5 GK stock fetuses.…”
Section: Resultssupporting
confidence: 92%
“…Western blot analysis Gel electrophoresis and immunoblotting for the detection of IGF2 and IGF1 receptor (IGF1R) were performed as previously described [16] and detailed in ESM Methods.…”
Section: Methodsmentioning
confidence: 99%
“…For example, genes coding for transcription factors crucial to the pancreatic beta cell-such as Neurog3, Nkx6.1, NeuroD2, and v-maf musculoaponeurotic fibrosarcoma oncogene homolog A (MafA)-were found to be putative binding targets for ZBED6 in myoblast cells (1). ZBED6-mediated control of IGF2 may be relevant to beta cells because it has been observed that aberrant IGF2 production in embryonic pancreas preceded the subsequent beta cell mass anomaly that develops in diabetic Goto-Kakizaki rats (3). Furthermore, the human insulin gene is clustered closely together with IGF2 (4), pointing to the possibility that not only IGF2, but also insulin might be controlled by a common ZBED6-dependent regulatory mechanism.…”
mentioning
confidence: 99%
“…In addition, as GK rats exhibit more than a 50% decrease in beta cell mass from fetal life onwards [10,11], we hypothesise that defective pancreatic vascularisation is associated with perinatal beta cell mass deficit. Indeed, vessel development, a major component of pancreatic islet development and function, is particularly active around birth [12][13][14] and altered programming of vascularisation has been shown to affect the development and function of various organs [15][16][17].…”
Section: Introductionmentioning
confidence: 94%
“…GK rats were bred in our own colony at the University Paris-Diderot, together with Wistar control rats from the GK strain derived after backcrossing of animals selected at the upper limit of normal distribution for glucose tolerance [19]. Characteristics of GK rats have been previously described [1,[4][5][6]10,11,[18][19][20][21]. At the indicated age, rats were weighed, bled at time of decapitation and blood, liver and pancreas collected for analysis.…”
Section: Animalsmentioning
confidence: 99%